(untitled) (Eurasian Medical Research Periodical, 2022)
Pregnant women’s health is one of the urgent issues of medical and social importance not only in Uzbekistan, but also in the countries of the world. In 2021, 3,500,000 cases of Covid-19 and 12,300 deaths among pregnant women worldwide. (worldometer.info). Methods. The clinical material for the study was obtained from the general blood analysis data of 26 pregnant women treated with post-covid syndrome in the department of pathology of pregnant women of the multidisciplinary clinic of the Tashkent Medical Academy during 2021